Lack of immunogenicity of hydrolysed wheat flour in patients with coeliac disease after a short‐term oral challenge. Issue 4 (19th June 2017) - Mandile, R.; Picascia, S.; Parrella, C.; Camarca, A.; Gobbetti, M.; Greco, L.; Troncone, R.; Gianfrani, C.; Auricchio, R.
Summary: Background: A gluten‐free diet is currently the only reliable therapeutic strategy that is approved for coeliac disease (CD). For many patients, however, compliance remains inadequate. Aim: To investigate the immunogenicity of wheat flour that was pre‐treated with selected lactobacilli and fungal proteases (hydrolysed wheat gluten) in coeliac patients. Methods: The immunogenicity of hydrolysed wheat gluten was evaluated both in vitro in intestinal T cell lines (TCLs) and in vivo in treated CD patients after a short‐term gluten challenge. Twenty treated CD patients were enrolled and equally randomised into two groups. The patients ate bread that was prepared with hydrolysed wheat flour or natural wheat flour (10 g of gluten/d for 3 days). The interferon (INF)‐γ responses to natural gliadin and a 33‐mer peptide were assessed by the enzyme‐linked immunospot (ELISPOT) assay on peripheral blood mononuclear cells (PBMCs) both before and 6 days after the start of the challenge. Results: Hydrolysed wheat was not able to activate the TCLs from the coeliac intestinal mucosa. Consistent with the in vitro results, no significant increase in INF‐γ secretion was observed in patients who consumed hydrolysed wheat flour. Conversely, the consumption of natural wheat gluten mobilised INF‐γ secreting cells in the blood ( P <.05). Conclusions: We confirm that fermentation of wheat flour with sourdough lactobacilli and fungal proteases is capable of abolishing the T cell immunogenicity of gluten in coeliac patients. Our data also validate the short‐term oral challenge as a useful tool for testing the efficacy of novel therapeutic approaches.